CORRELATING READING LITERACY AND WRITING LITERACY IN JUNIOR HIGH SCHOOL PEMATANGSIANTAR - Afifa May Shara; Dinda Andriani; Ayu Widya Ningsih; Kisno Shinoda (Journal of English Education, 2020)
Good literacy ability is one of the demands in learning 21st century. The purpose of this study was to find out the correlation between students' reading literacy ability and writing visual text ability for seventh grade students of SMP Negeri 1 Pematangsiantar. 133 respondents from 200 populations were randomly selected using simple random sampling technique. This is a quantitative research method using correlation research. Data collection used tests including multiple choice and essay. Using the Pearson products moment formula, this study analyzes data from both tests. The hypothesis of this research is H1 which states that there is a correlation between reading literacy ability and writing visual text ability and H0 states that there is no correlation between reading literacy ability and writing visual text ability. The results of this study indicate the correlation coefficient between the two variables is r =0.91 It means that there is a very strong relationship between reading ability and writing visual text ability. Based on the correlation coefficient, it can be concluded that H1 is accepted and H0 is rejected. Then, the coefficient of determination is symbolized by r2 is 0.83, it means the students' writing visual text ability is 83% influenced by reading literacy ability.